GRACE products and land surface models for estimating the changes in key water storage components in the Nile River Basin. Issue 6 (15th March 2021) - Nigatu, Zemede M.; Fan, Dongming; You, Wei
Highlights: Investigating hydrological dynamics is crucial for managing water resources. Performances of different GRACE products were evaluated. CSR mascon performed best among GRACE products. Nile River Basin groundwater and soil moisture trend shows a potential depletion. The two-month lag of GRACE Terrestrial water storage from rainfall was noted. Abstract: The Nile River Basin (NRB) is facing extreme demand for its water resources due to an alarming increase in population and the changing climate. The NRB is not compatible with ground-based in-situ observations owing to its large basin area size and limited hydrological data access from basin countries. Thus, it lends itself to remotely sensed approaches with high spatial resolution and extended temporal coverage. The Gravity Recovery and Climate Experiment (GRACE) avails a unique opportunity to investigate the changes in key components of terrestrial water storage (TWS). GRACE TWS solutions have specific tuning parameters and processing strategies that result in regionally specific variations and error patterns. We explored the TWS time series spatiotemporal changes, trends, uncertainties, and signal-to-noise ratio among different GRACE TWS data. We had also investigated the key terrestrial water storage components such as surface water, soil moisture, and groundwater storage changes. The results show that GRACE spherical harmonic solutions' uncertainty is higher than the mass concentration (mascon) over the NRB, and the Center for Space Research-mascons had the best performance. The evapotranspiration correlation (R 2  = 0.85) has the highest correlation with GRACE's TWS, whereas the normalized difference vegetation index (R 2  = 0.82) has the second highest correlation. Notably, significant long-term (2003–2017) negative groundwater and soil moisture trends demonstrate a potential depletion of the NRB. Despite an increase in precipitation and the TWS time series, the rate of decline increased rapidly after 2008, thereby indicating the possibility of human-induced change (e.g. for irrigation purposes). Therefore, the results of this study provide a guide for future studies related to hydro-climatic change over the NRB and similar basins.